Perancangan Ulang Alat Penguji Injektor Motor Diesel Menggunakan Metode Kaizen Di Lab Motor Diesel Jurusan Teknik Mesin Fakultas Teknik Universitas Negeri Surabaya: Perancangan Ulang Alat Penguji Injektor Motor Diesel Menggunakan Metode Kaizen Di Lab Motor Diesel Jurusan Teknik Mesin Fakultas Teknik Universitas Negeri Surabaya - ., Daud (Universitas Negeri Surabaya, 2019)
The function of the injector tester is used to measure spray pressure and inspect spray injector, and the fuction of redesign of the diesel motor injector test tool is also to make it easier for student of Mechanical Engineering Unesa to test without refilling the fuel that has been used and increase the safety of testing injector. In achieving the objectives, writer uses the Kaizen method. This method applies knowledge to find problems and potential improvements to the device to be designed to obtain information on the effectiveness of the redesign of the injector tester. The result of performance test diesel injector tester using Kaizen method show effective because the tool can test the pressure, leakage, and spray on the nozzle. Easy operation and maintenance, can be used as learning medium and can be developed. Keywords: Tester tool, Injection, Kaizen Method.